2022
DOI: 10.21203/rs.3.rs-1732538/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Water intake, hydration status and related hydration biomarkers among physically active male young adults in Beijing, China: a cross-sectional study

Abstract: Studies on the water intake of athletes in daily life are insufficient. The objective was to determine the water intake and hydration status among physically active male young adults. In this cross-sectional studies study, 111 physically active male young adults were recruited. The amount of daily total drinking fluid intake (TDF) among participants was recorded and evaluated in real time over 7 days using the “7-day 24-hour fluid intake questionnaire” (liq. In7). The daily water intake from food (WFF) was cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
1
3
3
Order By: Relevance
“…The study found that the hydration status of the participants may be closely related to their water intake, urination behavior, and urine indicators. Similar results were found in the research on young people in China [ 35 , 51 ]. The result of one study abroad found strong associations (| r | ≧ 0.6) between TDF and 24 h urine volume, osmolality, and USF among adults [ 3 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The study found that the hydration status of the participants may be closely related to their water intake, urination behavior, and urine indicators. Similar results were found in the research on young people in China [ 35 , 51 ]. The result of one study abroad found strong associations (| r | ≧ 0.6) between TDF and 24 h urine volume, osmolality, and USF among adults [ 3 ].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, judging by 24 h urine osmolality, only 16% of the participants were in the hydration status and 43% were in hypohydration status. Compared with the results of the previous study conducted among young adults in China, the proportion of athletes with hydration status was lower and the proportion with hypohydration status was higher [ 51 ]. There are no further studies on the water intake and hydration status of athletes in daily life in China.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations